Consumption of Whole Eggs Promotes Insulin Sensitivity in Db/db Mice (OR34-01-19). (13th June 2019) - Lu, Peiran; Wu, Lei; Guo, Xin; Wong, Siau Yen; Clarke, Stephen; Lucas, Edralin A; Smith, Brenda; Chowanadisai, Winyoo; Wang, Weiqun; Medeiros, Denis; Lin, Dingbo
Abstract: Objectives: Chicken eggs have a high nutrient density. Some country guidelines recommend that people with type 2 diabetes (T2D) limit their consumption of eggs due to its high cholesterol content. However, several clinical studies showed that egg intake is associated with a lower risk of type 2 diabetes. In the current study, we sought to explore whether egg consumption improves insulin sensitivity and subsequent blood glucose management in type 2 diabetic db/db mice. Methods: Six-week-old male db/db mice were fed a low-fat diet (LFD, 10 kCal % from fat) or LFD supplemented with 1% whole eggs (Egg) for 8 weeks. At the termination of the study, mice were fasted for 3 hrs prior to euthanization. Blood and other tissues were collected for laboratory assessments. Plasma metabolic parameters and pro-inflammatory cytokines were monitored by a clinical analyzer and ELISA, respectively. Hepatic and skeletal muscle mitochondrial respiratory activity was assessed by a Seahorse XF e Analyzer. Hepatic gene expression was analyzed by transcriptomics and confirmed by real-time PCR and/or Western blot. Results: Egg consumption significantly increased body weight gain, lowered fasting blood glucose, insulin, and IL-6 levels, and elevated total cholesterol, HDL, LDL, and GLP-1 levels. Only the basal mitochondrial respiratory activity was decreased, and the complex II respiratory activity was increased in gastrocnemius muscles in mice fed Egg. Hepatic mitochondrial activity was not altered by diet. Mechanistically, transcriptomics results revealed that hepatic genes involved in enhanced insulin sensitivity were highly expressed, but genes in endogenous cholesterol synthesis were significantly suppressed after egg consumption. Conclusions: The results suggest that egg consumption is beneficial to blood glucose control in type 2 diabetic mice. Type 2 diabetic animal could manage the cholesterol level through suppression of de novo cholesterol synthesis when consuming a high cholesterol diet, e.g., egg diet. Funding Sources: National egg nutrition center grant USDA NIFA grant